Immunohistochemical and morphometric evaluation of gastrocnemius muscle and myotendinous junction of golden retriever dogs with muscular dystrophy - Beretta, Daniel Côrtes (2014)
In this research we studied the alterations in the muscles and myotendinous junction of dogs with muscular dystrophy. Gastrocnemius muscle (GM) and myotendinous junction (MTJ) samples of 3 controls and 6 dystrophic dogs were subjected to histopathological and immunohistochemical assays. Histopathological/histomorphometric analysis showed that the lesions in the GM were more pronounced and showed the highest percentage of Fiber Type II (FTII) and low values for the minimum diameters and areas of Fiber Type I (FTI) and FTII than those in the MTJ. FTII in dystrophic MTJ was morphologically similar to the controls. There was a significant difference (p < 0.07) in the MHCI antigen compared to the control. We conclude that the preservation of the morphological features of the MTJ can be directly related to a better stabilization of FTII, lower expression of the MHCI complex and less cytotoxic activity of CD8.